Mild forms of herpes encephalitis. Issue 11 (November 1984) - Klapper, P E; Cleator, G M; Longson, M
Abstract : Three cases of herpes encephalitis are described. A definite diagnosis was established and all patients made a good recovery without specific antiviral chemotherapy. These reports are representative of those forms of herpes encephalitis with a good prognosis. It is suggested that the introduction of rapid non-invasive procedures will indicate a higher incidence of herpes encephalitis than is presently accepted. The relevance of repeated episodes of herpes encephalitis with respect to the aetiology of some psychiatric disorders and in the evaluation of antiviral agents is also discussed.